Legal Gaps in Regulation and Criminal Liability for the Use of Personal Mobility Devices on Sidewalks and Roads - Sapta Eka Yanto; Dwi Kusumo Wardhani (Siber Nusantara Research, 2026)
The development of micro-transportation technology has given rise to Personal Mobility Devices (PMDs) as a new mode of mobility increasingly used in public spaces, both on sidewalks and on roads. The presence of PMDs raises legal issues because the Indonesian traffic law system does not yet provide clear and comprehensive regulations regarding the status, usage space, and criminal liability mechanisms for users. Law Number 22 of 2009 concerning Traffic and Road Transportation still relies on conventional vehicle classifications, placing PMDs in a normative area that is not explicitly addressed. The condition creates legal uncertainty, difficulty in enforcement, and potential violations of the safety of pedestrians and other road users. This study aims to analyze the nature of the legal vacuum in PMD regulations, examine the weaknesses of the applicable criminal liability construction, and formulate the need for more adaptive traffic law reform. The research method employed is normative legal research with statutory, conceptual, and comparative legal approaches. A comparative analysis was conducted on PMD regulations in Singapore, the United Kingdom, Germany, and France to identify a proportional and safety-oriented regulatory model. The results reveal that a purely repressive approach through criminal law is ineffective when applied to PMDs and risks excessive criminalization. This study recommends reforming traffic law through special regulations on Personal Mobility Devices (PMD) that prioritize administrative and preventive approaches, along with selective criminal sanctions to ensure legal certainty and public safety.